2015
DOI: 10.1074/jbc.m115.643072
|View full text |Cite
|
Sign up to set email alerts
|

NsrR from Streptomyces coelicolor Is a Nitric Oxide-sensing [4Fe-4S] Cluster Protein with a Specialized Regulatory Function

Abstract: Background: NsrR family proteins are [2Fe-2S] or [4Fe-4S] cluster-containing global regulators.Results: Streptomyces coelicolor NsrR regulates only three genes, and it is the [4Fe-4S] form of the protein that binds tightly to NsrR-regulated promoters.Conclusion: [4Fe-4S] NsrR has a specialized function associated only with nitric oxide stress response.Significance: Members of the NsrR family are most likely all [4Fe-4S] proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
167
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(184 citation statements)
references
References 61 publications
(104 reference statements)
17
167
0
Order By: Relevance
“…Electron paramagnetic resonance and resonance Raman spectroscopies demonstrated that NO interaction with iron in the [4Fe-4S] cluster causes dinitrosylation of iron, leading to the dissociation of NsrR from the nasD promoter DNA (11). The direct modification of the [4Fe-4S] cluster by NO has also been reported with an NsrR ortholog (12).…”
mentioning
confidence: 90%
“…Electron paramagnetic resonance and resonance Raman spectroscopies demonstrated that NO interaction with iron in the [4Fe-4S] cluster causes dinitrosylation of iron, leading to the dissociation of NsrR from the nasD promoter DNA (11). The direct modification of the [4Fe-4S] cluster by NO has also been reported with an NsrR ortholog (12).…”
mentioning
confidence: 90%
“…This is useful, particularly for protein identification, and for characterisation of post-translational covalent modifications, but it does not provide information about non-covalently bound cofactors. However, the coupling of soft electrospray ionisation (ESI) with solution and ionization conditions under which proteins remain folded has provided important new insights into non-covalent interactions for a range of biomolecules [69][70][71][72], including several Fe-S cluster proteins, where the cluster bound forms of the protein was detected [58,73,74]. Early studies reported the use of ESI and ion cyclotron resonance MS to study [4Fe-4S] ferredoxins [73].…”
Section: Electrospray Ionisation Mass Spectrometrymentioning
confidence: 99%
“…More recently, improvements in the resolution offered by Time Of Flight (TOF) mass analysers enables the cheaper ESI-TOF instruments to provide information about the type of cluster bound by Fe-S proteins. Although ionisation conditions require optimisation on a protein to protein basis, characterisation of two Fe-S regulatory proteins has been reported recently [58,74] and clearly this technique has potential for studying the reactivity of these clusters, including with NO.…”
Section: Electrospray Ionisation Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…NsrR is an NO-sensitive repressor from the Rrf2 family that contains an [Fe-S] cluster. The cluster is likely to be [4Fe-4S], and reaction with NO is accompanied by a decrease in DNA binding affinity and de-repression of NsrR-regulated promoters (Bodenmiller & Spiro, 2006;Tucker et al, 2008;Yukl et al, 2008;Crack et al, 2015). The previously characterized NsrR regulon includes genes encoding the NO-scavenging flavohaemoglobin (hmp), the RIC (repair of iron centres) protein that participates in the repair of NO-damaged [Fe-S] clusters (ytfE), the respiratory nitrite reductase Nrf that is also an NO reductase (nrfABCDEFG), genes involved in motility ( fliA) and aromatic amine metabolism (tynA, feaB), and genes of unknown function, for example ygbA, yccM and yeaR-yoaG (Bodenmiller & Spiro, 2006;Filenko et al, 2007;Lin et al, 2007;Rankin et al, 2008;Partridge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%